ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI SISTEM INFORMASI AKUNTANSI PADA DIRA SHOPPING CENTRE DI JEMBER - Tutut Winarsih; Hamzah Fansuri Jusuf; Lia Rachmawati (Jurnal Ilmiah Akuntansi Indonesia, 2021)
ABSTRACTThis study aims to analyze the factors that influence the implementation of the accounting information system at CV. DIRA GROUP in Jember. The objects of research include Dira Shopping Center Ambulu, Dira Shopping Center Balung, and Dira Shoppng Center Kencong.The population in this study were employees who worked at the Dira Shopping Center in Jember. This research method used validity and reliability tests. The classic assumption test which consists of a normality test and a multicolonierity test. Multiple linear regression analysis and determination test.Hypothesis testing is simultaneous test (f test) and partial test (t test). The results showed that user involvement, personal technical skills, top management support, formalization of system development, training and education had a positive effect on the performance of the accounting information system. This shows that if user involvement, personal technical skills, top management support, formalization of systemdevelopment, training and education greatly support the performance of the accountinginformation system to work optimally.Keywords: User Involvement, Personal Engineering Skills, Top ManagementSupport, System Development Formalization, Training and Education, and Accounting Information System Implementation